Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Pemadam Kebakaran dan Penyelamatan Kota Depok - Zilaika Firsta Kautzariana,; Helmy Ivan Taruna, (Journal of Management and Creative Business, 2024)
This research aims to analyze the influence of work motivation and work discipline on the performance of Depok City Central Fire Department employees. Data was obtained from the results of questionnaires, literature studies, and observations related to the research objectives. The analysis technique uses multiple linear regression using the SPSS version 29 application. The results of partial hypothesis testing (T Test) on the variables Work Discipline (X1) and Work Motivation (X2) show t count > t table, namely 0.973 < 0.681 and a significance value of 0.974 > 0.5 means that the Work Discipline variable has a significant and influential effect on the Employee Performance variable at the Depok City Fire Department. The results of simultaneous hypothesis testing (F Test) on the two variables Work Discipline (X1) and Work Motivation (X2) show the calculated f value for the number of respondent samples of 40 people using the incidental sampling technique. The results show that the variables of motivation and work discipline do not have a significant effect, either partially or simultaneously, on the performance of Depok City Fire Department employees.